Biopolitics at the End of Life and Ethical-Theological Reflection (Revista Iberoamericana de Bioética, 2020)
During the last Spanish election campaign, some political proposals raised the possibility of developing end-of-life legislation. This text seeks to provide an overview of all relevant issues within the subject and the role that might be played by theological reflection in the public discussion regarding this topic.First, certain anthropological assumptions —related to the concept of person, their individual dignity and responsibilities based on their social status— are highlighted. Then, we recollect the uncertain nature of medical data and the inadequacy of legislation on many occasions.Finally, we point out the effort made by moral theology to rationalise and update its contributions. It would be unfair and irrational to not consider these suggestions as equally valid as those of any other philosophical approach.
Keywords: biopolitics; euthanasia; theological bioethics